2015
DOI: 10.1001/jamasurg.2014.3572
|View full text |Cite
|
Sign up to set email alerts
|

Overtreatment of Young Adults With Colon Cancer

Abstract: Young adults with colon cancer received significantly more postoperative systemic chemotherapy at all stages, but they experienced only minimal gain in adjusted survival compared with their older counterparts who received less treatment. This mismatch suggests that attention should be given to long-term cancer survivorship in young adults with colon cancer because they likely face survivorship needs that are distinct from those of their older counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
139
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(155 citation statements)
references
References 35 publications
12
139
2
2
Order By: Relevance
“…Second, our finding that young NHB individuals diagnosed with stage II colon cancer have a 60% to 70% higher risk of death compared with NHWs is interesting in light of existing data demonstrating that adjuvant therapy in stage II cancers is of marginal benefit (associated with improvements in overall survival of 5% or less). 28 In a recent nationwide cohort study of 13,102 patients diagnosed with CRC between the ages of 18 and 49 years, Kneuertz et al 15 found that young patients were significantly more likely than older patients to receive multiagent systemic chemotherapy at all disease stages, suggesting a trend toward overtreatment of young patients. Because use of adjuvant chemotherapy in stage II CRC is often at the discretion of the treating oncologist, it is possible that differences in the treatment of stage II cancers may contribute to racial disparities in survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our finding that young NHB individuals diagnosed with stage II colon cancer have a 60% to 70% higher risk of death compared with NHWs is interesting in light of existing data demonstrating that adjuvant therapy in stage II cancers is of marginal benefit (associated with improvements in overall survival of 5% or less). 28 In a recent nationwide cohort study of 13,102 patients diagnosed with CRC between the ages of 18 and 49 years, Kneuertz et al 15 found that young patients were significantly more likely than older patients to receive multiagent systemic chemotherapy at all disease stages, suggesting a trend toward overtreatment of young patients. Because use of adjuvant chemotherapy in stage II CRC is often at the discretion of the treating oncologist, it is possible that differences in the treatment of stage II cancers may contribute to racial disparities in survival.…”
Section: Discussionmentioning
confidence: 99%
“…12 Young patients are more likely than their older counterparts to present with regional or distant disease, and although some studies have suggested that CRCs behave more aggressively in young patients, 13,14 others have demonstrated improved disease-specific survival compared with individuals diagnosed at older ages. 15-17 …”
Section: Introductionmentioning
confidence: 99%
“…While some studies showed poorer survival for young patients as compared to their older counterparts, 6, 7 others found better or comparable survival among younger patients. 813 …”
Section: Introductionmentioning
confidence: 99%
“…Since prognosis of colon cancer among young patients is not well known, it is difficult to advise about adjuvant chemotherapy, 13 and treatment options for patients with young-onset CRC remain unclear. 24 Thus, overuse of chemotherapy may be more likely for younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Treating all Stage II patients is “overtreatment” 3 , as a small subset derives any therapeutic benefit, whereas others experience harm, a poorer quality of life, and no net benefit 4 . Prior attempts at identifying the subset of high-risk Stage II colon cancer patients have not been robust 5 , underscoring the need to discover prognostic and predictive biomarkers that can facilitate the selection of patients for additional treatment.…”
mentioning
confidence: 99%